2012
DOI: 10.4028/www.scientific.net/amm.165.252
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Application of Driving Simulators for Research and Training Activities in Malaysia

Abstract: Driving simulators (DS) are extensively used worldwide as tools in research and training related to driving behaviour and road safety. However, DS have yet to be used extensively in Malaysia. While there is no guarantee that the use of DS may have direct positive impact on road safety, it offers an objective and insightful opportunity to measure and understand driving behaviour. This is especially relevant in Malaysia as it struggles to reduce the high number of fatalities due to road crashes. This paper revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…VE is an environment simulated by a computer as a real environment or an imaginary environment which is displayed on a computer screen which is often placed in special equipment like driving simulators. Simulator sickness could contaminate the data collected through the driving simulator as what it will be capturing is unlikely to be participant's actual behavior (Ariffin et al, 2012). Out of 30 respondents, only 3.3% (n=1) of them reported that they experienced simulator sickness by using MiDOF.…”
Section: Simulator Sickness Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VE is an environment simulated by a computer as a real environment or an imaginary environment which is displayed on a computer screen which is often placed in special equipment like driving simulators. Simulator sickness could contaminate the data collected through the driving simulator as what it will be capturing is unlikely to be participant's actual behavior (Ariffin et al, 2012). Out of 30 respondents, only 3.3% (n=1) of them reported that they experienced simulator sickness by using MiDOF.…”
Section: Simulator Sickness Reductionmentioning
confidence: 99%
“…However in Malaysia, the applications of simulator are only used for research and training. Both application using three type of simulator are used in Malaysia which are low-cost, medium cost and high cost (Ariffin et al, 2012). A typical development of a driving simulator requires the integration of several subsystem such as control inputs from car cabin, vehicle mathematical model, scenario development, visual display, auditory display, steering feel characteristics, performance measurement and data storage (Eskandarian, 2014).…”
Section: Introductionmentioning
confidence: 99%